Step-by-step explanation:
![\sqrt{(x + 6) ^{2} } = \sqrt{18} \\ x + 6 = + - \sqrt{18} \\ x + 6 = + - \sqrt[3]{2}](https://tex.z-dn.net/?f=%20%5Csqrt%7B%28x%20%2B%206%29%20%5E%7B2%7D%20%7D%20%20%3D%20%20%5Csqrt%7B18%7D%20%5C%5C%20x%20%2B%206%20%3D%20%20%2B%20%20-%20%20%5Csqrt%7B18%7D%20%20%5C%5C%20x%20%2B%206%20%3D%20%20%2B%20%20-%20%20%5Csqrt%5B3%5D%7B2%7D%20)
Answer:
123.94
Step-by-step explanation:
The answer is $2.35
if u add $1.25 and $2.35 you get $3.60
then u multiply $3.60 by 5 which gives you 18
Negative 73
drop of 73
minus 73
below 73
taking away 73
Answer:
2304
Step-by-step explanation:
<u>Given :- </u>
- A geometric sequence is given to us which is 9 , -18 , 36.
And we need to find out the 9th term of the sequence. Here firstly we should find the Common Ratio and then we can substitute the respective values in the formula to find the nth term of a geometric sequence .
<u>Common Ratio :- </u>
CR = -18÷ 9 = -2
<u>The </u><u>9</u><u> th term :- </u>
T_n = arⁿ - ¹
T_9 = 9× (-2) ⁹ - ¹
T_9 = 9 × (-2)⁸
T_9 = 9 × 256
T_9 = 2304
<u>Hence the 10th term is </u><u>2</u><u>3</u><u>0</u><u>4</u><u>.</u>